Notes to Literature: Volume One - Adorno, Theodor W. 1903-1969; Tiedemann, Rolf; Weber Nicholsen, Shierry (New York Columbia University Press, 1992)
These 17 essays by an important European critic of the Frankfurt school deal with a broad range of topics: the essay form, the epic, the narrator in the contemporary novel, lyric poetry and society, surrealism, Beckett's Endgame , and various European authors (Balzac, Goethe, Proust, Valery, Bloch, Heine, etc.). The essays are generally pitched at a rather high level of abstraction and with a Marxist philosophical slant: the response of literature and individual artists to alienation in an industrial/capitalist society is a recurring concern. Though this is primarily a book for specialists and academic libraries, Adorno's thought and highly suggestive remarks are well worth the effort.- Richard Kuczkowski, Dominican Coll., Blauvelt, N.Y.
Originally published in 1958
Keywords: Philosophy; Literature